Hydration testing in collegiate wrestlers undergoing hypertonic dehydration - Bartok, C.; Schoeller, D. A.; Sullivan, J. C.; Clark, R. R.; Landry, G. L. (Medicine & Science in Sports & Exercise, 2004)
Because dehydration (DEH) violates assumptions used in the assessment of body composition, hydration testing has become an integral part of minimal weight (MW) assessment. PURPOSE: To determine the accuracy of hydration tests for the detection and quantification of hypertonic DEH. METHODS: Twenty-five male collegiate wrestlers (mean +/- SD, age: 20.0 +/- 1.4 yr, height: 175.0 +/- 7.1 cm, body mass: 81.7 +/- 15.3 kg) had their hydration assessed under well-controlled conditions of euhydration (EUH) and DEH. The DEH phase occurred on the same day as EUH, after subjects acutely dehydrated 2-6% of body weight through fluid/food restriction and exercise in a hot environment. RESULTS: All hydration tests except plasma potassium significantly increased from EUH to DEH, and meaningful cutoff values could be established for most tests. Cutoff values for urine tests were 586 mOsm.L(-1) for osmolality and 71 mEq.L(-1) for potassium. Plasma cutoff values were 293 mOsm.L(-1) for osmolality, 140 mEq.L(-1) for sodium, 103 mEq.L(-1) for chloride, and 3.5 pg.mL(-1) for arginine vasopressin. For ratio tests, a urine:plasma osmolality of 2.06 and an extracellular:intracellular water of 0.533 measured by the bioelectrical impedance spectroscopy were cutoff values. For urine specific gravity, a cutoff value of 1.020 g.mL(-1) had a sensitivity and specificity of 96% each for the automated harmonic oscillation technique and 87% and 91% (respectively) for the dipstick technique. Protein (by dipstick) was detected in 5% of subjects in EUH, and 100% of subjects in DEH. Correlations between hydration tests and dehydration were only low to moderate. CONCLUSION: This study supports a specific gravity cutoff of 1.020 g.mL(-1) for the identification of hypertonic DEH. Future research should test the cutoff values established in this study and explore the relationship between DEH and urine protein.